Proclamations of the Granada of the nineteenth century (1810-1831) - Rojo Gallego-Burín, Marina (Cuadernos de Historia del Derecho, 2018)
In this article we transcribe 37 administrative documents. These texts were destined to be placed in public places in order to allude to other norms, to communicate circumstances creating of obligations for the population or to participate in events that affected them. For the first time these texts are compiled, in response to the political becoming of the Granada between the years 1810 and 1831, one of the most intense periods of the city.